Treatment of Municipal Wastewater by Hollow Fiber Dynamic Membrane Bioreactors - Isik, Onur; Orman, Irem; Abdelrahman, Amr Mustafa; Ersahin, Mustafa Evren; Ozgun, Hale; Demir, Ibrahim; Koyuncu, Ismail (Wiley, 2022)
AbstractIn this study, an aerobic membrane bioreactor (MBR) with a polyester fabric hollow fiber filter is used for municipal wastewater treatment. This polyester fabric filter is used as support material for dynamic membrane formation in the MBR. High treatment performance is obtained in the permeate achieving over 93% of chemical oxygen demand removal efficiency and low particulate material concentration (<10 mg L−1). The system is operated for 58 d without any clogging. The average transmembrane value is found as around 598 mbar after the system reaches stable conditions. Morphological analyses including confocal laser scanning microscopy, environmental scanning electron microscopy, energy‐dispersive X‐ray, and Fourier transform infrared spectroscopy are performed to obtain a detailed understanding of the cake layer formation. The use of hollow fiber dynamic membranes can provide compact membrane volume with high surface area, thus, the volume of the reactor can be further decreased.